Transcriptome Changes in Hirschfeldia incana in Response to Lead Exposure - Auguy, Florence; Fahr, Mouna; Moulin, Patricia; El Mzibri, Mohamed; Smouni, Abdelaziz; Filali-Maltouf, Abdelkarim; Béna, Gilles; Doumas, Patrick (Frontiers in Plant Science, 2016)
Hirschfeldia incana, a pseudometallophyte belonging to the Brassicaceae family and widespread in the Mediterranean region, was selected for its ability to grow on soils contaminated by lead (Pb) .The global comparison of gene expression using microarrays between a plant susceptible to Pb (Arabidopsis thaliana) and a Pb tolerant plant (Hirschfeldia incana) enabled the identification of a set of specific genes expressed in response to lead exposure. Three groups of genes were particularly over-represented by the Pb exposure in the biological processes categorized as photosynthesis, cell wall and metal handling. Each of these gene groups was shown to be directly involved in tolerance or in protection mechanisms to the phytotoxicity associated with Pb. Among these genes, we demonstrated that MT2b, a metallothionein gene, was involved in lead accumulation, confirming the important role of metallothioneins in the accumulation and the distribution of Pb in leaves. On the other hand, several genes involved in biosynthesis of ABA were shown to be up-regulated in the roots and shoots of H. incana treated with Pb, suggesting that ABA-mediated signaling is a possible mechanism in response to Pb treatment in H. incana. This latest finding is an important research direction for future studies.